Multiple reproductives in nests of the Neotropical termite Constrictotermes cyphergaster (Isoptera, Termitidae, Nasutitermitinae) - Hélida Ferreira da Cunha (Revista Brasileira de Entomologia, 2002)
Constrictotermes cyphergaster (Silvester, 1901) builds arboreal nests in Brazilian Cerrado stricto sensu, which are frequently cohabited by inquilines termites and by termitophiles. In a study made at the Parque Estadual da Serra de Caldas Novas, Goiás, Brazil, there were four nests with multiple reproductives, and secondary reproductives were found in 26 nests. Nymphs of Inquilinitermes were more abundant (9,47%) than nymphs of C. cyphergaster (0,78%).